Cost control measures and their impact on profitability of manufacturing companies: a case study of Primeseed.co - Vambe, Gregy (Midlands State University, 2018)
This study sought to analyze cost control measures and their impact on profitability of manufacturing companies. An increase in cost (operational and production costs) which added to reduced profitability in the manufacturing sector produced the need to address the problem through this research. The study was limited to cost control in manufacturing industry and as such it did not extend to other sectors of the economy. It was based on the assumption that all the responses from the company Primeseed.co represented other manufacturing companies. Descriptive research approach was used to fully satisfy the objective of the study as it gave the researcher to obtain important and useful data which was valid and reliable. Quantitative and Qualitative approaches were used to collect data. Primary data was obtained from a target population of 30 employees from departments of Primeseed.co. Major research findings showed that cost control measures have a positive impact on the profitability of manufacturing companies as reducing costs directly reflect an increase in the level of profits of an organization, it was evident that element of costs such as materials, labor and overhead costs and workers behavior could be strategically controlled with measures like budgetary control, standard costing and variance analysis, accounting to achieve higher profit levels. In controlling costs a good cost control system is required to minimize costs as wastages is eliminated and inefficiencies reduced during production and throughout an organization. Also from the findings, increase in labor costs, material wastages, increase in repairs and maintenance cost and decrease in operational performance were the effects of implementing weak cost control techniques.